2017
DOI: 10.4012/dmj.2016-264
|View full text |Cite
|
Sign up to set email alerts
|

Enamel microcracks in terms of orthodontic treatment: A novel method for their detection and evaluation

Abstract: The study aimed at introducing current available techniques for enamel microcracks (EMCs) detection, and presenting a method for direct quantitative analysis of an individual EMC. Measurements of the detailed EMCs characteristics (location, length, and width) were taken from the reconstructed images of the buccal tooth surface (teeth extracted from two age groups of patients) employing a scanning electron microscopy (SEM) and our derived formulas before and after ceramic brackets removal. Measured parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Group control showed a high percentage (58.3%) of EMC, some of which were ramified and extended apical and incisal to the bracket area, as described also by Dumbryte [18,19]. This group displayed a minor area of enamel loss that appeared only on the SEM observations.…”
Section: Enamel Topographymentioning
confidence: 52%
“…Group control showed a high percentage (58.3%) of EMC, some of which were ramified and extended apical and incisal to the bracket area, as described also by Dumbryte [18,19]. This group displayed a minor area of enamel loss that appeared only on the SEM observations.…”
Section: Enamel Topographymentioning
confidence: 52%
“…Several qualitative and quantitative methods have been used to diagnose alterations on enamel surfaces subjected to ceramic bracket bonding, including SEM, optical stereomicroscopy (with or without a digital camera), a magnifying lens (10×) and transillumination with a fiber optic light head, and 3D OCT scanning (Ahrari et al, 2012; Kitahara-Céia et al, 2008; Bishara et al, 2008; Dumbryte et al, 2015, 2017; Janiszewska-Olszowska et al, 2015; Leão Filho et al, 2015; Machoy et al, 2019). To date, SEM has been the method most widely used for the evaluation of enamel quality after ceramic bracket debonding.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed an association between the ceramic bracket debonding process and increases in the length (Heravi et al, 2008;Dumbryte et al, 2016Dumbryte et al, , 2017 and width (Dumbryte et al, 2016(Dumbryte et al, , 2017 of enamel microcracks. Recently, a systematic review pointed out that although quantitative studies show weak evidence because of the lacking of parameter number analysis, there is strong evidence for the increasing of the enamel microcracks after debonding (Dumbryte et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Future research should focus on the effect of cryopreservation itself on enamel. Interesting methods using SEM were described by Dumbryte et al 32) .…”
Section: Discussionmentioning
confidence: 99%